Promoting quality assurance through provision of electronic information resources in Nigerian library schools (2016)
Nigerian library and information science (LIS) schools are professional institutions that train students in the various aspects of information profession. These include the creation, selection, organization, management, preservation, dissemination and utilization of collections of information resources in all formats. Nigerian LIS schools play a significant role in the production of high quality LIS professionals who occupy a unique position in national development. Adequate provision of resources especially in electronic format for students’ use will translate into quality delivery of knowledge in the profession. Inadequate information and communication technology (ICT) skills, low basic information literacy levels, prohibitive cost to gain access to the internet, inadequate ICT infrastructure, inadequate affordable online access to the internet amongst others are the constraints faced by Nigerian LIS schools in the provision of electronic information resources, thereby hampering quality assurance in the profession. This reveals a need for great efforts by LIS schools in Nigeria to promote quality assurance through provisions of opportunities to meet the basic learning needs of LIS students for the emerging global society. This paper therefore discusses Nigerian LIS schools, electronic information resources, as well as their values in LIS schools in Nigeria for promoting quality assurance.